(untitled) (Research, Society and Development, 2022)
Breast cancer is the most common among women. Screening actions aim to reduce morbidity and mortality from this neoplasm, identifying tumors in early stages to improve the chances of rehabilitation and cure. Objective: to analyze whether there was a reduction or increase in mammography rates in the 2020-2021 biennium compared to the 2018-2019 biennium in Brazil, its Regions, and Federation Units. Method: through DATASUS population projection data and SUS-approved mammograms in women aged 50 to 69 years, in the years 2018 to 2021, the coverage rates of examinations by women achieved and the reduction or increase of these rates were calculated. between biennia. Results: in general, Brazil showed a reduction of about 30% of exams in 2020/2021 compared to 2018/2019. In the South Region, the greatest reduction was observed: 33% fewer mammograms, while the North Region presented the smallest: approximately 11% reduction. Among the Federation Units, there was an increase in mammograms performed during the pandemic in the Federal District (25%), Roraima (15%), Pará (5%) and Amapá, which reached 3,228%, in contrast to the others. States, which showed a reduction in the same period. Conclusion: there was a national reduction of about 30% in the number of mammograms approved by the SUS in the 2020-2021 biennium compared to 2018-2019. Despite this, the Federal District, Roraima, Pará and Amapá showed positive rates, which may indicate good public health actions aimed at screening, which could be replicated in future policies by the other states.